SINDROM PASCA COVID-19 - Aprilia Sari; Yeni Mahwati (Jurnal Sehat Masada, 2023)
Background: The phenomenon of post-COVID-19 syndrome is still largely unreported in Indonesia. Post-COVID-19 syndrome itself has not been widely studied, resulting in a lack of promotive and preventive measures for patients who experience post-COVID-19 syndrome. Objective: To determine the syndrome experienced by COVID-19 survivors and the factors that influence the occurrence of post-COVID-19 syndrome. Methods: Literature search using Google Scholar and Pubmed databases with a range of years 2019-2023. With keywords "Adult" and "Elderly" and "Long COVID-19" or "COVID-19 Syndrome" or "Long haulers" or "Post COVID-19" and "Brain fog" or "Fatigue" or "Dyspnea" or "Breathlessness". Discussion: A total of 10 studies were included. The most reported syndrome was fatigue and the most reported risk factor affecting the incidence of post COVID-19 syndrome was female gender. Conclusion: Post-COVID-19 syndrome is a complex condition with multiple and prolonged syndromes. The effects of post-COVID-19 syndrome are enormous for health.